ChemInform Abstract: Tin‐Functionalized Azobenzenes as Nucleophiles in Stille Cross‐Coupling Reactions. Issue 31 (5th August 2014) - Strueben, Jan; Gates, Paul J.; Staubitz, Anne
Abstract An easy, mild, and selective method to prepare stannylated azobenzenes is described.